Suberoylanilide hydroxamic acid inhibits growth of head and neck cancer cell lines by reactivation of tumor suppressor microRNAs - Datta, Jharna (Oral Oncol, 2016)
BACKGROUND: microRNAs negatively regulate gene expression at the post-transcriptional level. Mounting evidence shows that miR expression is deregulated in human cancers including head and neck squamous cell carcinoma (HNSCC). Epigenetically silenced tumor suppressor miRs may be re-expressed upon treatment with histone deacetylases inhibitors. Suberoylanilide Hydroxamic Acid (SAHA) is a histone deacetylase inhibitor that is currently being investigated in clinical trials for HNSCC. We hypothesized that SAHA will re-express a set of tumor suppressor miRs and enhance the efficacy of cisplatin and radiation in HNSCC. RESULTS: In this study, miR expression profile was utilized to identify the tumor suppressor miRs that are re-expressed following SAHA treatment in HNSCC. Our data demonstrated that two tumor suppressor miRs, miR-107 and miR-138, were significantly up-regulated in CAL27 and SCC25 cell lines, following SAHA treatment. In addition to this, treatment with SAHA in a dose dependent manner significantly inhibited the cell proliferation, cell migration, and anchorage dependent clonogenic survival in CAL27 and SCC25 cell lines, respectively. Further, the expression of several oncogenes, PKCε, HIF1β, CDK6, and RhoC were down regulated in response to SAHA treatment. Additionally, we demonstrated that the combination treatment with SAHA and a chemotherapeutic drug cisplatin caused a significant reduction of cell growth compared to the single agent treatment. CONCLUSION: Our data indicate that SAHA treatment results in reactivation of the silenced tumor suppressor miRs. Furthermore, this study emphasizes the usefulness of this drug as a novel combination therapy for HNSCC patients.